Students’ Stress and Anxiety Analysis based on the Demographic Factors - Lulu Fatihatul Uyun; Sisca Wulandari; Nurul Setiani; Ilfi Intansari; Angel Putri; Jamiu Temitope Sulaimon (Universitas Sarjanawiyata Tamansiswa, 2024)
Students frequently face difficulties in academic management causing mental health disorders such as anxiety, stress, and even depression. This research aims to describe the level of stress and anxiety experienced by students. The current study applied a descriptive quantitative with a non- probability sampling procedure and a saturated sampling technique on 27 students as its respondents. The Depression Anxiety Stress Scale 21 (DASS 21) was used to measure the stress and anxiety level with the respect of age, job, and residence.